2020
DOI: 10.4018/jeco.2020040102
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving Consumer Engagement and Intentions with Gamification of Mobile Apps

Abstract: The advent of smartphones revolutionized and took the market to a new level. Now a days, majority of internet users spend their maximum time on smartphones, specifically on mobile apps. The emergence of numerous apps in smartphones with games features has brought about a different trend, mobile app gamification. The emerging popularity of smartphone technologies and their mobile apps have led various companies to engage their consumers with mobile apps, specifically through gamification. Therefore, companies g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 59 publications
(7 reference statements)
2
24
0
Order By: Relevance
“…Similarly, Huang et al found that perceived ease of use and value positively impacted user satisfaction with a gamified system. 30 While we determined that students were motivated by the value they identified in the system, perceived ease of use did not significantly impact that value. To complete assignments in Classcraft®, students downloaded a Microsoft Word (Redmond, Washington, USA) document, filled it in and then uploaded it back to the system.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Huang et al found that perceived ease of use and value positively impacted user satisfaction with a gamified system. 30 While we determined that students were motivated by the value they identified in the system, perceived ease of use did not significantly impact that value. To complete assignments in Classcraft®, students downloaded a Microsoft Word (Redmond, Washington, USA) document, filled it in and then uploaded it back to the system.…”
Section: Discussionmentioning
confidence: 91%
“…The differences between our study and those mentioned may be context. While we examined motivations to use a gamified system in higher education, the aforementioned studies were conducted with a fitness app (Huang et al 30 ) and mobile game apps (Kamoj et al 29 ). The motivation to use those types of apps differs from educational gamified systems in both the reasons for use and the value seen in them.…”
Section: Discussionmentioning
confidence: 99%
“…The same can be said about gamification, with its advantages supported by some literature (Alsawaier 2018;Hamari et al 2014;Huseynov and Dhahak 2020). A research gap continues to exist when the need arises to validate whether the use of gamified applications as tools for engagement and brand attitude effectively represent a gain for organizations and consumers (Kamboj et al 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Once the games 'ability to effectively retain the players' attention is validated, it becomes interesting to associate this context with the theme of customer engagement in a digital component. Therefore, it is necessary to prove whether the combination of the two translates into a gain in brand attitude (Alsawaier 2018;Kamboj et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Samsung is achieving significant success in many ways, but if the company increases its social marketing and communication, it will be able to achieve significant success in South Korea and other areas (Choi, 2015). In the current market scenario, as Kamboj et al (2020) suggested, factors which enhance consumer engagement and interactive covalue creation with a concept of gamification, especially via development of various mobile apps for the younger users. From the interactive process with the consumers, Samsung can deepen understanding of the market.…”
Section: Key Theme Two 'Understanding the Market: How To Enhance Digimentioning
confidence: 99%